Alpha-adrenergic pathways in the lateral hypothalamus are important for the dipsogenic effect of carbachol injected into the medial septal area - Callera, J. C. [UNESP]; Saad, W. A. [UNESP]; Camargo, L. A.A. [UNESP]; Menani, J. V. [UNESP]; Renzi, A. [UNESP]; Abrao-Saad, W. [UNESP] (My University, 1995)
We studied the effect of the α1- and α2-adrenergic receptors of the lateral hypothalamus (LH on the control of water intake induced by injection of carbachol into the medial septal area (MSA) of adult male Holtzman rats (250-300 g) implanted with chronic stainless steel cannulae into the LH and MSA. The volume of injection was always 1 μl and was injected over a period of 30-60 s. For control, 0.15 M NaCl was used. Clonidine (20 nmol) but not phenylephrine (160 nmol) injected into the LH inhibited water intake induced by injection of carbachol (2 nmol) into the MSA, from 5.4 ± l.2 ml/h to 0.3 ± 0.1 and 3.0 ± 0.9 ml/h, respectively (N = 26). When we injected yohimbine (80 nmol) + clonidine (20 nmol) and prazosin (40 nmol) + clonidine (20 nmol) into the LH, water intake induced by injection of carbachol into the MSA was inhibited from 5.4 ± 1.2 ml/h to 0.8 ± 0.5 and 0.3 ± 0.2 ml/h, respectively (N = 19). Water intake induced by carbachol (2 nmol) injected into the MSA was decreased by previous injection of yohimbine (80 nmol) + phenylephrine (160 nmol) and prazosin (40 nmol) + phenylephrine (160 nmol) from 5.4 ± 1.2 ml/h to 1.0 ± 0.7 and 1.8 ± 0.8 ml/h, respectively (N = 16). The cannula reached both the medial septal area in its medial portion and the lateral hypothalamus. It has been suggested that the different pathways for induction of drinking converge on a final common pathway. Thus, adrenergic stimulation of α2-adrenoceptors of LH can influence this final common pathway.
Keywords: α1- and α2-adrenoceptors; cholinergic receptors; lateral hypothalamus; septal area; water intake